2016
DOI: 10.1128/aac.02650-15
|View full text |Cite
|
Sign up to set email alerts
|

Doravirine Suppresses Common Nonnucleoside Reverse Transcriptase Inhibitor-Associated Mutants at Clinically Relevant Concentrations

Abstract: Doravirine (DOR), which is currently in a phase 3 clinical trial, is a novel human immunodeficiency type 1 virus (HIV-1) nonnucleoside reverse transcriptase inhibitor (NNRTI). DOR exhibits potent antiviral activity against wild-type virus and K103N, Y181C, and K103N/Y181C mutant viruses, with 50% inhibitory concentrations (IC 50 s) of 12, 21, 31, and 33 nM, respectively, when measured in 100% normal human serum (NHS). To assess the potential for DOR to suppress NNRTI-associated and rilpivirine (RPV)-specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 22 publications
6
76
0
Order By: Relevance
“…Blood for elbasvir and grazoprevir plasma analysis was collected on day 10 of period 2 and day 5 of period 3 at the following time points: predose and at 0. 5,1,2,3,4,5,6,8,12,16, and 24 h postdose.…”
Section: Methodsmentioning
confidence: 99%
“…Blood for elbasvir and grazoprevir plasma analysis was collected on day 10 of period 2 and day 5 of period 3 at the following time points: predose and at 0. 5,1,2,3,4,5,6,8,12,16, and 24 h postdose.…”
Section: Methodsmentioning
confidence: 99%
“…dine and tenofovir disoproxil fumarate (TDF) (4,5). In vitro, doravirine has similar activity against HIV-1 wild-type virus and the K103N, Y181C, and K103N/Y181C mutants (6). Previously reported results showed that doravirine is metabolized primarily to an oxidative metabolite, M9, by cytochrome P450 3A4 (CYP3A4) and, to a lesser extent, by CYP3A5 ( Fig.…”
mentioning
confidence: 89%
“…This mutation confers a high degree of resistance to both NVP and DLV and a moderate resistance to rilpivirine RPV [11]. A relatively rare mutation of Y188L was also identified in viruses from patients who have failed with NNRTI-containing regimens.…”
Section: Introductionmentioning
confidence: 99%